Syngas production from palm oil mill effluent via catalytic steam reforming - Kim, Hoong Ng; Yoke, Wang Cheng; Zhan, Sheng Lee; Cheng, C. K. (Universiti Malaysia Pahang, 2018)
This paper reports on the novel application of catalytic steam reforming process to convert palm oil mill effluent (POME) into syngas over a 20wt%Ni/80wt%Al2O3 catalyst. In Malaysia, palm oil industry is the most important agro-based industry, with a total production of 37.2 million tons of crude palm oil for the past two years [1]. During the palm oil extraction, more than 50% of the water consumed would end up as wastewater, commonly known as palm oil mill effluent (POME). In Malaysia, POME waste is considered as one of the major sources of water due to the inefficiency of widely-adopted open ponding treatment system. POME has high organic loading, with reported mean biochemical oxygen demand (BOD) and chemical oxygen demand (COD) values of 25000 ppm and 51000 ppm [2].